Kajian Entomologi dalam Mendukung Pengendalian Malaria melalui Program Flying Health Care (FHC) di Kabupaten Yahukimo, Provinsi Papua - Tri Ramadhani; Amirullah Amirullah; Rahmat Rahmat (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2021)
Flying Health Care is one of the programs of the Ministry of Health to accelerate the elimination of malaria in an integrated manner, especially in the Yahukimo Regency. The purpose of this activity is to describe the role of entomological aspects in malaria control efforts. The data includes cases of malaria, mosquitoes and Anopheles larvae, breeding place, and vector control efforts. Data was collected by observation, survey, and secondary data analysis. The results of the study show that malaria cases rank first out of 10 diseases in health facilities. Malaria cases were more common occurred at the age of 10-19 years, male and near to health facilities. Breeding places in the form of swamps and puddles in the environment around patients with water depths ranging from 5-30 cm. There is no entomological data at the district level or at Puskesmas Aplim. Ongoing vector control efforts are in the form of distributing insecticide-treated mosquito nets. Insecticide mosquito nets have not been fully distributed to the community, this is constrained by the existing infrastructure in health care facilities. Vector control efforts should be supported by the results of entomological surveys and it is important to do socialization on how to use and maintain mosquito nets at the time of mosquito net distribution.